Up and down the cline-- the nature of grammaticalization - Fischer, Olga; Norde, Muriel, 1968-; Perridon, Harry (Typological studies in language, 2004)
The basic idea behind this volume is to probe the nature of grammaticalization. Its contributions focus on the following questions: (i) In how far can grammaticalization be considered a universal diachronic process or mechanism of change and in how far is it conditioned by synchronic factors? (ii) What is the role of the speaker in grammaticalization? (iii) Does grammaticalization itself provide a cause for change or is it an epiphenomenon, i.e. a conglomeration of causal factors/mechanisms which elsewhere occur independently? (iv) If it is epiphenominal, how do we explain that similar pathway.